1993
DOI: 10.1105/tpc.5.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Bean Defense Responses by Pseudomonas syringae.

Abstract: We have developed a model system to examine suppression of defense responses in bean by the compatible bacterium Pseudomonas syringae pv phaseolicola. Previously, we have shown that there is a general mechanism for the induction of the bean defense genes phenylalanine ammonia-lyase (PAL), chalcone synthase (CHS), chalcone isomerase (CHI), and chitinase (CHT) by incompatible, compatible, and nonpathogenic bacteria. Here, we show that bean plants infiltrated with isolates of P. s. phaseolicola failed to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…In a very early study, Jakobek and colleagues showed that Pseudomonas syringae pv. phaseolicola has evolved strategies to suppress the expression of defense genes such as phenylalanine ammonia-lyase, chalcone synthase, chalcone isomerase and the production of phytoalexins in bean [53]. In addition, microscopic studies revealed that localized cell wall modification and associated papillae formation were caused by Xcv hrp- mutants but not by the wild type strain [54].…”
Section: Discussionmentioning
confidence: 99%
“…In a very early study, Jakobek and colleagues showed that Pseudomonas syringae pv. phaseolicola has evolved strategies to suppress the expression of defense genes such as phenylalanine ammonia-lyase, chalcone synthase, chalcone isomerase and the production of phytoalexins in bean [53]. In addition, microscopic studies revealed that localized cell wall modification and associated papillae formation were caused by Xcv hrp- mutants but not by the wild type strain [54].…”
Section: Discussionmentioning
confidence: 99%
“…Although they can trigger immune receptor function, pathogen-encoded effector proteins, including bacterial T3Es, have evolved to promote virulence (Jakobek et al, 1993). Once delivered, effector proteins are trafficked to various sub-cellular locations (Nomura et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The actions and targets of P. syringae effectors that promote pathogenicity remain elusive (Staskawicz et al ., 2001). However, there were early indications that P. syringae could suppress the induction of defence related transcripts during infections on host plants (Jakobek et al ., 1993). Recent studies show that several P. syringae effectors contain biologically active cysteine protease catalytic triads similar to those found in YopJ and YopT from animal pathogenic Yersinia species (Orth et al ., 2000; Shao et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%